Adhesion/growth-regulatory galectins tested in combination: evidence for formation of hybrids as heterodimers - Miller, Michelle C.; Ludwig, Anna-Kristin; Wichapong, Kanin; Kaltner, Herbert; Kopitz, Jürgen; Gabius, Hans-Joachim; Mayo, Kevin H. (Biochemical journal, 2018)
The delineation of the physiological significance of protein (lectin)-glycan recognition and the structural analysis of individual lectins have directed our attention to studying them in combination. In this report, we tested the hypothesis of hybrid formation by using binary mixtures of homodimeric galectin-1 and -7 as well as a proteolytically truncated version of chimera-type galectin-3. Initial supportive evidence is provided by affinity chromatography using resin-presented galectin-7. Intriguingly, the extent of cell binding by cross-linking of surface counter-receptor increased significantly for monomeric galectin-3 form by the presence of galectin-1 or -7. Pulsed-field gradient NMR (nuclear magnetic resonance) diffusion measurements on these galectin mixtures indicated formation of heterodimers as opposed to larger oligomers. 15N-1H heteronuclear single quantum coherence NMR spectroscopy and molecular dynamics simulations allowed us to delineate how different galectins interact in the heterodimer. The possibility of domain exchange between galectins introduces a new concept for understanding the spectrum of their functionality, particularly when these effector molecules are spatially and temporally co-expressed as found in vivo.
Gesehen am 20.04.2020